Will the Global Minimum Tax Hurt Developing Countries? - Andreas Haufler; Hirofumi Okoshi; Dirk Schindler (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study the effects that the introduction of the Global Minimum Tax (GMT) has from the perspective of developing countries. Our model features two asymmetric host countries for FDI that compete with each other for the location of multinational firms, and simultaneously fight profit shifting to a tax haven. The developing country has the weaker enforcement technology to fight profit shifting; it therefore loses more revenue from profit shifting, but also becomes a more attractive location for multinationals. The GMT reduces both profit shifting and the tax-avoidance advantage of the developing country. If tax competition for real investment is sufficiently severe, the introduction of the GMT reduces tax rates and tax revenues in the developing country while tax revenues in the developed country rise. Our results help explaining the opposition of developing countries to the GMT.
Keywords: F23; H26; 330; global minimum tax; developing countries; tax competition